Influence of Independent Variables on Employee Performance in Aceh's Cultural and Tourism Office - Sufitrayati Sufitrayati; Zainuddin Zainuddin; Rita Ningsih; Susanti Susanti (International Conference on Multidisciplinary Research, 2022)
This research aims to find out the influence of accounting information systems, internal supervision, and the completeness of tasks on the performance of employees in the Aceh Cultural and Tourism Office. The object of this research is all employees of the office of the Aceh Culture and Tourism Bureau, as many as 186 employees, 36 employees use Sloven technology to draw samples as the result. The sample used in this study is multiple linear regression analysis. As a result of the research, the accounting information system, internal supervision, and completion of tasks simultaneously and partially affect the performance of employees at the Aceh Cultural and Tourism Office.The correlation coefficient (R) value of 0.595 shows that the correlation (relationship) between free variables and bound variables by 59.5% is that the performance of employees in the work of the Aceh Cultural and Tourism Office has a moderate and positive correlation with the system of accounting issues, internal supervision and task complement age of 87.6%. While the coefficient of determination (R2) of 0.445, is that any changes in employee performance variables can be explained by changes in accounting information system variables, internal supervision, and task completeness of 0.445 or 44.five% and the remaining 55.five% explained by other variables beyond the origin of this study can affect employee performance such as leadership style, financial accounting system, internal control system, financial management, and others. Keywords: Employee Performance, Accounting Information Systems, Internal Supervision, and Task Completion.